Strategi Supervisi untuk Meningkatkan Kedisiplinan Guru dalam Mengelola Aktivitas Pembelajaran - Muhammad Hartono (Aslama: Jurnal Pendidikan Islam, 2025)
This study focus on the unproductive behaviors exhibited by teachers during classroom instruction. It differs from from previous research by specifically highlighting and analyzing the types of unproductive activities carried out by teachers during the learning process, efforts to improve discipline through supervision to reduce such behaviors, and the effectiveness of supervision in shaping time discipline and teaching performance. The objective of this study is to thoroughly examine the nature of unproductive activities performed by teachers during instruction, explore the role of supervision in promoting discipline and reducing these behaviors, and assess the effectiveness of supervision in fostering time management and professional teaching conduct. This research employs a library research method and applies a qualitative approach, in which data is gathered through an in-depth review of books, articles, academic journals, undergraduate theses, and relevant reports that discuss the issues examined in this study. The data analysis technique follows the the Miles and Huberman model, which includes three main stages: data reduction, data display, and verification and conclusion drawing. The conclusion of this study is that supervision serves as an effective strategy to improve teacher discipline. Supervision should be conducted in a planned and structured manner not only as a means of monitoring but also as a process of understanding and guiding teachers to adopt professional attitudes and improve the quality of their instruction. Therefore, supervision is not merely about control, but is a powerful tool for shaping professionalism, work culture, and overall teaching quality.